Complications among Postpartum Mothers in Indonesia - Elisa Ulfiana; Tandiyo Rahayu; Yuni Wijayanti; Dina Nur Anggraini Ningrum (Jurnal Kesehatan Masyarakat, 2026)
The postpartum period, also known as the postpartum period, begins immediately after the birth of the neonate and placenta and ends at 6–8 weeks. Maternal mortality in Indonesia was caused by bleeding in 30.5%, infection in 22.5%, gestosis in 17.5%, and anesthesia in 2.0%. The purpose of this study is to analyze the risk factors that affect the incidence of complications in postpartum mothers in the working area of the Grobogan Health Center in 2025. This research is quantitative with a case control study design,using data from the Grobogan Health Center in 2025. The analysis used was univariate, bivariate (chi-square test), and multivariate analysis (logistic regression). The results showed that there was a relationship between maternal education (p=0.011, OR=1.83), employment status (p<0.0001, OR=2.52), gestational age (p<0.0001, OR=3.02), parity status (p=0.034, OR=1.24), BMI (p<0.0001, OR=9.09), childbirth distance (p<0.0001,OR=13.38), hypertension (p=0.006, OR=2.4), diet (p<0.0001, OR=5.797) and exposure to cigarette smoke (p<0.0001, OR=3.50), history of psychological disorders (p=0.007,OR=0.158), and LBW (p<0.0001, OR=2.443). The results of this study are expected to increase postpartum mothers’ awareness of the importance of recognizing and  managing risk factors that may lead to complications, thereby encouraging healthy behaviors and informed decision-making during the postpartum period.